PENGARUH TERAPI PURSED LIP BREATHING MENIUP BALON TERHADAP STATUS OKSIGENASI ANAK DENGAN ASMA - Eva Oktaviani; Ririn Putri Damaiyanti; M Vaizul Rahman; Kusrini Kusrini (Coping: Community of Publishing in Nursing, 2021)
Asthma is a serious global health problem and can affect all age groups, including children. Asthma symptoms in children can be controlled with complete management, not only by administering pharmacological therapy but also using non-pharmacological therapy. Non-pharmacological therapy can help control asthma attacks, namely through breathing exercises. Breathing exercises can be pursed lip breathing through balloon blowing therapy. The purpose of this study was to determine the effectiveness of the pursed lip breathing technique by blowing a balloon on the oxygenation status of children with asthma. The research design was pre_posttest group design. Oxygenation status in the form of respiratory rate, pulse, oxygen saturation measured before and after pursed lip breathing therapy. Pursed Lip Breathing is carried out for 15 minutes with 4 breaths of inspiration and 7 times of expiration, pausing between cycles of 2 seconds. The research sample consisted of 25 children taken by purposive sampling. The research sites are in the villages of Maur Baru and Maur Lama, Muara Rupit District, Musi Rawas Utara District. The analysis used the Wilcoxon test on respiratory rate, and oxygen saturation. The dependent statistical t-test was used on the pulse frequency variable. There was a significant difference in oxygenation status before and after pursed lip breathing by blowing a balloon. Pursed lip breathing has proven to be effective as a non-pharmacological therapy that can be applied routinely to improve oxygenation status in children with asthma, so as to optimize lung mechanical function.